Radiation‐Hard and Ultralightweight Polycrystalline Cadmium Telluride Thin‐Film Solar Cells for Space Applications. Issue 11 (5th October 2016) - Yang, Gwangseok; Cho, Eun Woo; Hwang, Yun Jeong; Min, Byoung Koun; Kang, Yoonmook; Kim, Donghwan; Kim, Jihyun
Abstract: Achieving high‐specific‐power and radiation hardness of solar cells is of great importance to perform tasks and achieve duration in space. Therefore, we investigated the proton irradiation resistance of ultralightweight CdS/CdTe thin film solar cells having high specific power values. High‐energy proton beams (15 MeV) with doses ranging from 1×10 12 to 1×10 15 cm −2 were used, equivalent to more than 2000 years in low Earth orbit. Although 70 % decrease in cell conversion efficiency was observed after proton irradiation with dose of 1×10 15 cm −2, it still maintained the photovoltaic performance. The specific power of the fabricated cell decreased from 358 W kg −1 to 109 W kg −1 after proton irradiation (dose=1×10 15 cm −2 ), which is still comparable to specific powers of other types of solar cells. Our work indicated that reduction of short circuit current is a major factor of deterioration of the cell performance under the high energy proton irradiation. This work revealed that our lightweight CdS/CdTe solar cells have significant potential for the use in space applications: reduction of launch cost by achieving high specific power and assurance of durability over prolonged space missions. Abstract : Apt for aerospace applications : Ultralightweight thin‐film cadmium telluride (CdTe) solar cells are tested in realistic space conditions. The cells demonstrate remarkable radiation hardness for outer‐space tasks. Even after severe proton irradiation, corresponding to over 2000 years in low earth orbit, they achieve high specific power values. Such high radiation hardness shows the feasibility of the CdTe solar cells for long‐term space missions.